Adaptive to learner educational systems - Baskas, Antanas (Lietuvos matematikos rinkinys, 2023)
Most educational systems take into account learner features like goals/tasks, knowledge, background, hyperspace experience, preferences and interests. However, less attention has been paid to the fact that people have different approaches to learning, namely that the individuals perceive and process information in very different ways. Recent researches are trying to alleviate this and integrate learning styles in the design of their adaptive applications.